2008
DOI: 10.1063/1.2969048
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancement of critical current density and flux pinning properties of Gd-doped (Bi, Pb)-2212 superconductor

Abstract: The enhanced critical current density (JC) and flux pinning properties of Bi1.7Pb0.4Sr2-xGdxCa1.1Cu2.1O8+δ (where x=0.0, 0.1, 0.2, and 0.3) system prepared by solid-state synthesis in bulk polycrystalline form were studied. Phase analysis, microstructural investigation, and superconducting characterization were performed to evaluate the relative performance of the samples. The x-ray diffraction and energy dispersive spectroscopy analyses show that Gd atoms are successfully doped in place of Sr in the system. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Further, although the Bi-2212 materials play an important role on the preparation of long wires and tapes, the applications of them in magnetic field and high temperatures are reported to limit because of their structural layer, very low charge carrier density, strong anisotropic properties, extremely short coherence length (n) and large penetration depth (k) [16,18]. Similarly, the Bi-2212 superconductors have relatively poor mechanical properties, limiting the use of these materials in most of practical applications [19]. Hence, several methods have been studied to improve these properties of the materials for years.…”
Section: Introductionmentioning
confidence: 98%
“…Further, although the Bi-2212 materials play an important role on the preparation of long wires and tapes, the applications of them in magnetic field and high temperatures are reported to limit because of their structural layer, very low charge carrier density, strong anisotropic properties, extremely short coherence length (n) and large penetration depth (k) [16,18]. Similarly, the Bi-2212 superconductors have relatively poor mechanical properties, limiting the use of these materials in most of practical applications [19]. Hence, several methods have been studied to improve these properties of the materials for years.…”
Section: Introductionmentioning
confidence: 98%
“…Resistive dissipation causes a variety of problems, which include reduced efficiency of transmission lines, and noise in superconductivity based devices. At low temperatures and currents, the inhomogenities, dislocations, grain-boundaries and rough surfaces are the sources of intrinsic pinning in a superconductor material [5][6][7][8][9]. This pinning locks the vortices in place and reduces the resistance.…”
Section: Introductionmentioning
confidence: 97%
“…Because the activation energy is the potential barrier height, it is the measure of flux pinning strength of the superconductor. In most of the existing reports, the activation energy is determined from the thermally assisted flux creep theory described by the Arrhenius equation [13,14] However, in HTS the increase in width of the resistive transition in magnetic field is a direct consequence of thermal fluctuations in the vortex system [8,11,12,15]. Hence one should consider both temperature and magnetic field dependent pinning analysis for a meaningful estimation of activation energy of the superconductor.…”
Section: Introductionmentioning
confidence: 98%
“…Also the Pb-substituted Bi-2212 [(Bi, Pb)-2212] has shown enhanced J C s in applied fields, compared to the Pb-free Bi-2212 [7]. Again a few studies reported that the flux pinning strength of (Bi, Pb)-2212 increases by rare-earth (RE) doping [8][9][10] and the flux pinning ability is usually determined from the values of flux pinning force density and activation energy [8,11,12]. Because the activation energy is the potential barrier height, it is the measure of flux pinning strength of the superconductor.…”
Section: Introductionmentioning
confidence: 99%